The Russian Memoirs About Battle at Austerlitz - S. P. Ribakov (Vestnik MGIMO-Universiteta)
Development Russian memoires, to the devoted wars 1805-1807 and Patriotic war of 1812 in much depended on changes of public interest to these events, and also from censorship. In campaign of 1805 emperor Alexander I was after Peter I epoch the first of Russian rulers, Which itself was at war and has endured defeat of allied armies at Austerlitz (nowadays Slavkov, The Czech republic). To the moment of issue in the end of 1860th of L.N.Tolstogo of the novel, scenes of battles Schongrabern and Austerlitz weren't known to the general reader. Here analysis attempt is given me – Moires of participants Austerlitz: general А.F.Langeron, general А.Kh. Eyler, Diplomat А.Czartoryski.